Connecting over the internet: Establishing the therapeutic alliance in an internet-based treatment for depressed adolescents. (July 2022) - Mortimer, Rose; Somerville, Matthew P.; Mechler, Jakob; Lindqvist, Karin; Leibovich, Liat; Guerrero-Tates, Brenda; Edbrooke-Childs, Julian; Martin, Peter; Midgley, Nick
Internet-based treatments have been developed for youth mental health difficulties, with promising results. However, little is known about the features of therapeutic alliance, and how it is established and maintained, in text-based interactions between adolescents and therapists in internet-based treatments. This study uses data collected during a pilot evaluation of a psychodynamic internet-based therapy for depressed adolescents. The adolescents had instant-messaging chats with their therapists once a week, over 10 weeks. The adolescents also rated the therapeutic alliance each week, using the Session Alliance Inventory. The present study uses qualitative methods to analyse transcripts of text-based communication between the young people and their therapists. The aim is to identify and describe the key features of therapeutic alliance, and reflect upon the implications for theory and clinical practice. Analysis identified three 'values' that may underpin a strong therapeutic alliance: togetherness, agency and hope. A number of therapist techniques were also found, which seemed to create a sense of these values during text-chat sessions. These findings are discussed, alongside implications for future research.